Computational Thinking and Mathematical Problem Solving in Madrasah Tsanawiyah Students - I Made Suarsana; Tatang Herman; Elah Nurlaelah; Didi Suryadi; Irianto Irianto; Al Jupri; Asep Bayu Dani Nandiyanto; Zulkaidah Nur Ahzan (Jurnal Pendidikan Islam, 2026)
The integration of computational thinking into mathematics learning is increasingly important in preparing students for problem-solving in the digital era, and visual programming tools such as Flowgorithm offer potential pedagogical support. This study analyzes the effect of Flowgorithm-assisted instruction on students’ computational thinking skills and mathematical problem-solving abilities. A quasi-experimental pretest–posttest control group design was employed and implemented in two phases: a programming phase and a mathematics learning phase. The population consisted of all eighth-grade students at Madrasah Tsanawiyah in Bali Province, Indonesia, from which 34 students were selected using cluster random sampling (20 in the experimental group and 14 in the control group). Data on computational thinking and mathematical problem-solving abilities were collected using achievement tests and analyzed using MANCOVA, followed by post hoc tests, with effect sizes reported using partial eta squared. The findings reveal significant differences between the experimental and control groups, with post hoc analysis indicating that Flowgorithm-assisted mathematics learning significantly improved students’ computational thinking skills, while no significant difference was found in mathematical problem-solving abilities. Despite a non-significant effect on problem-solving, the integration of Flowgorithm showed no negative impact, suggesting that Flowgorithm-assisted instruction can be a viable approach for embedding computational thinking concepts into mathematics curricula and instructional practices.